Borrowed Discourse-Pragmatic Features in Kenyan English. Issue 2 (4th May 2022) - Muro, Loveluck; Unuabonah, Foluke
Abstract: This article explores five discourse-pragmatic features— si, sijui, eish, kumbe, and kweli— which are borrowed from African languages into Kenyan English, in order to examine their sources, meanings, frequencies, spelling adaptation, collocational patterns, positioning, syntactic distribution, and discourse-pragmatic functions. The data, which are extracted from the Kenyan components of the International Corpus of English-East Africa and the Global Web-based English corpus, are analysed quantitatively and qualitatively, from a postcolonial corpus pragmatic framework. The results show that the borrowed discourse-pragmatic features are infrequent, orthographically stable, favour clause-initial position, and rarely co-occur with other discourse-pragmatic features. Si, sijui, and kweli are pragmatic markers used to request confirmation of shared knowledge, indicate uncertainty, and emphasise the truth value in a proposition, respectively. Eish and kumbe are interjections which are mainly used to express emotions of irritation and surprise, respectively. This study extends the research on the discourse-pragmatic features of Kenyan English.